The Sage handbook of social marketing - Hastings, Gerard; Angus, Kathryn; Bryant, Carol A. (Los Angeles Sage, 2011)
"For the first time, this benchmark Handbook brings together a systematic framework and state of the art thinking to provide complete coverage of the social marketing discipline. The Handbook presents a major retrospective and prospective overview of social marketing, helping to define and shape its current and future developments by: examining the defining elements of social marketing, their intellectual origins, evolution, current status and direction of travel; discussing how these have been used in practice, emphasizing emerging areas and recent innovations; and, setting the agenda for future research and development in the discipline. For academics, this book will fill the gap in comprehensive social marketing literature, while being of interest to policymakers and graduate marketing and health studies students alike as it explores the idea that tools used to market fast-moving consumer goods and financial services can also be applied to pressing social problems, such as HIV/AIDS and global warming."--Provided by publisher.
Introduction: A Movement in Social Marketing Gerard Hastings -- Section 1: Theoretical debates -- Theoretical Models of Behaviour Change / Rob Donovan -- Social Models for Social Marketing / R. Craig Lefebvre -- Social Diffusion, Social Networks, Social Capital, Social Determinants and Social Franchising Relationship Marketing and Social Marketing / Susana Marques and Christine Domegan -- Understanding Social Norms / Patrick Kenny and Gerard Hastings -- Upstream and Downstream Applications For Social Marketers Design Thinking, Demarketing and Behavioural Economics / R. Craig Lefebvre and Philip Kotler -- Fostering Interdisciplinary Growth in Social Marketing Critical Marketing / Michael Saren -- Theoretical Underpinnings New Approaches Towards Resistance to Persuasion / Petia K. Petrova and Robert B. Cialdini -- Section 2: Marketing planning -- Segmentation and Targeting / Lynne Doner Lotenberg, Carol Schechter and John Strand -- Competition and Positioning / Gary Noble and Debra Z. Basil -- The Social Marketing Mix -- A Critical Review / Ken Peattie and Sue Peattie -- Communications in Social Marketing / Dana L. Alden, Michael D. Basil and Sameer Deshpande -- New Media in Social Marketing / Darren Mays, James B. Weaver and Jay M. Bernhardt -- Section 3: Research: it's roles and techniques -- Evaluation in Social Marketing / Martine Stead and Robert J. McDermott -- Qualitative Research Methods In Social Marketing / Simone Pettigrew and Michele Roberts -- Measurement in Quantitative Methods / Fiona J. Harris -- Section 4: Dancing with the Devil -- Critical Marketing / Janet Hoek -- Applications Social Marketing's Response to the Alcohol Problem / Sandra C. Jones -- Who's Conducting the Orchestra? From Social Marketing to Corporate Social Marketing -- changing consumption habits as the new frontier of Corporate Social Responsibility / Guido Pallazo -- Ethical Challenges in Commercial Social Marketing / Thomas Anker and Klemens Kappel -- Internal Social Marketing / Anne M. Smith -- Lessons From the Field of Services Marketing -- Section 5: Upstream and social change -- Impoverished Consumers and Social Marketing / Ronald Paul Hill -- Social Marketing and International Development / Georgina Cairns, Bruce Mackay and Laura MacDonald -- Social Marketing for a Sustainable Environment / Sue Peattie and Ken Peattie -- Business as Unusual / Jeff French -- The Contribution of Social Marketing to Government Policy Making and Strategy Development -- Section 6: Social marketing in practice: case studies -- Social Marketing and Advocacy / William D. Novelli and Boe Workman -- Social Marketing and Tobacco Control / Timothy Dewhirst and Wonkyong Beth Lee -- Social Marketing and the Health Educator / Robert J. McDermott, Kelli R. McCormack Brown and Rosemary Thackeray -- Social Marketing / William Smith -- A Future Rooted in the Past / William Smith.
Electronic reproduction.
Keywords: Social marketing -- Handbooks, manuals, etc; Behavior modification; Electronic books